2017
DOI: 10.1161/jaha.116.005387
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tenofovir Use With Risk of Incident Heart Failure in HIV‐Infected Patients

Abstract: BackgroundThe antiretroviral medication, tenofovir disoproxil fumarate (TDF), is used by most human immunodeficiency virus–infected persons in the United States despite higher risks of chronic kidney disease. Although chronic kidney disease is a strong risk factor for heart failure (HF), the association of TDF with incident HF is unclear.Methods and ResultsWe identified 21 435 human immunodeficiency virus–infected patients in the United States Veterans Health Administration actively using antiretrovirals betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…The level of viral suppression may be inferior to that noted in more updated registries and clinical trials. However, this level of viral suppression is comparable to that reported in other contemporary observational clinical cohort studies (56% to 62%) (11,20,22), and the viral suppression reported in our study is similar to that reported in a study by Hanna et al (39) involving more than 7,196 PHIV from the same geographic location during the same time period (66%). Therefore, a potential explanation for the worse outcomes in PHIV is poor adherence to treatment for either HIV or HF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The level of viral suppression may be inferior to that noted in more updated registries and clinical trials. However, this level of viral suppression is comparable to that reported in other contemporary observational clinical cohort studies (56% to 62%) (11,20,22), and the viral suppression reported in our study is similar to that reported in a study by Hanna et al (39) involving more than 7,196 PHIV from the same geographic location during the same time period (66%). Therefore, a potential explanation for the worse outcomes in PHIV is poor adherence to treatment for either HIV or HF.…”
Section: Discussionsupporting
confidence: 92%
“…There are no data on the association between PI-based regimens and outcomes specifically among PHIV with HF, a group at high risk of adverse events. Chen et al (20), in a study involving 21,435 PHIV, demonstrated an association between current use of tenofovir (a nucleoside reverse transcriptase inhibitor) and an approximately 30% to 40% lower risk of incident HF compared with past users or never users of this drug. In that study, patients with HF were excluded, and the effect of PI regimens was not the focus; however, a significant proportion of the comparator group was prescribed a PI-based ART regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overall viral suppression rate in this study was 51%. This rate of viral suppression is comparable to other contemporary observational clinical cohort studies (suppression rates of 45%–62%)1, 5, 38 and studies in this region (viral suppression rate of 58%),39 but is lower than observed in more recent registries and clinical trials 40, 41, 42. It is also possible that the PHIV with an ICD were sicker for other reasons, such as concomitant infections/lower CD4 cell count, and therefore more likely to have an ICD discharge.…”
Section: Discussionsupporting
confidence: 86%
“…Among a large cohort of HIV‐infected patients actively using antiretrovirals between 2002 and 2011, TDF use was strongly associated with lower risk of heart failure incidents. Compared with never users of TDF, current users of TDF and patients whose initial regimen included TDF had reductions in heart failure risk ranging from 30% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Among the NRTIs, tenofovir disoproxil fumarate (TDF) was approved by the American and European drugs regulatory authorities and was available for HIV treatment in 2002. Since its approval, this drug has been included in most recommended regimens and has been the most widely used NRTI for many years based on its established high efficacy and generally good tolerance, as demonstrated in clinical trials and real‐life studies …”
Section: Introductionmentioning
confidence: 99%